“No, pero si yo quisiera lo podría hacer”: Mitigating Concessive Resources in Argumentative Acts in the PRESEEA Corpus of Santiago, Chile - Ibarra Herrera, Daniela (2022)
This paper analyses concessive resources with a mitigating function which are found in argumentative acts in the PRESEEA corpus from Santiago, Chile. Based on data from 36 semi-structured interviews, the behaviour of concessive-oppositional moves and concessive discourse particles in argumentative acts is analyzed, and their sociolinguistic variation is described in relation to the speakers’ gender, age and level of education. The key findings highlight that in Chilean Spanish there are at least 12 strategies that fulfill a mitigating concessive function, among which “sí, pero (yes, but) + negation”, “aunque (even though)”, “no, pero (no, but) + assertion” and “a pesar (de) que (despite the fact that)” stand out. These strategies are linked to the functions of self-protection and face prevention in the development of the argumentative act. Furthermore, it is also observed that the variation is mostly due to the subject’s age.